The class III POU domain protein Brn-1 can fully replace the related Oct-6 during Schwann cell development and myelination. - Wegner, Michael; et al. (Molecular and Cellular Biology, 2005)
For differentiation, Schwann cells rely on the class III POU domain transcription factor Oct-6, which is expressed transiently when Schwann cells have established a one-to-one relation with axons but have not yet started to myelinate. Loss of Oct-6 leads to a transient arrest in this promyelinating stage and a delay in myelination. Although the closely related POU domain protein Brn-2 is coexpressed with Oct-6 in Schwann cells, its loss has only mild consequences. Combined loss of both POU domain proteins, in contrast, dramatically increases the myelination delay, raising the question of how related POU domain proteins compare to each other in their activities. Here, we have replaced Oct-6 expression in the mouse with expression of the class III POU domain protein Brn-1. Although this protein is not normally expressed in Schwann cells, Brn-1 was capable of fully replacing Oct-6. Brn-1 efficiently induced Krox-20 expression as a prerequisite for myelination. Onset and extent of myelination were also indistinguishable from that of the wild type in mice that carried only Brn-1 instead of Oct-6 alleles. Similar to Oct-6, Brn-1 down-regulated its own expression at later stages of myelination. Thus, class III POU domain proteins can fully replace each other in Schwann cell development.
UnivIS-Import:2015-03-09:Pub.2005.med.IB.LPCIPDBI.thecla